Harakî Salafism in Norway: ‘The Saved Sect’ Hugs the Infidels - Ulrika Mårtensson (Tidsskrift for Islamforskning, 2014)
The article is a study of the Norwegian Salafi organization Islam Net, which aims at defining Islam Net in terms of recent research on European Salafism and assessing its capacity for public civic engagement. With reference to de Certeau’s concept of discourse, and Habermas’ concepts of democratic legitimacy and religion in the public sphere, it is found that Islam Net’s capacity for civic engagement is severely restricted by its non-acceptance of human rights-based values, since this non-acceptance justifies for public institutions to deny the organization presence and refuse dialogue with Islam Net. From Habermas’ viewpoint this is a potential democratic deficiency, since it may weaken the legitimacy of democracy among Islam Net’s members.